KONTRIBUSI POWER OTOT TUNGKAI DENGAN LARI CEPAT (SPRINT) 100 METER PADA ATLET PUSAT PENDIDIKAN LATIHAN PELAJAR (PPLP) RIAU - Hirzan Rahmadon; Agus Sulastio; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:Based on the author's observations on the athletes of the Riau Student Training Education Center (PPLP) found symptoms in the 100-meter sprint, including when running, the speed of stepping on the lower foot and the sole of the foot against the ground contact is not optimal, the speed of steps and stride length is stillslow and less than the maximum. This study aims to determine the contribution of leg muscle power with a 100 meter sprint to the Riau Student Training Center Athlete (PPLP). The population in this study was the athletic female athlete Lancing kuning, totaling 7 people. The sampling technique used is total sampling. Thus, the sample of this study was female athletes, totaling 7 people. The instrument is a leg muscle explosive power test using a Standing Broad device and a speed of 100 yards. The data obtained were analyzed using the Product moment Correlation technique. Based on the results of research and data processing using research statistical procedures, it can be concluded that for the relationship between variable x and variable y, the value of r = 0.388 is obtained, then rxy < rtable is (0.388 < 0.811), then Ha is rejected, in other words there is no relationship There is a significant relationship between leg muscle power and 100 meter sprint at the Riau Student Training Center Athlete (PPLP). Leg muscle power contributed to the 100 meter run, which was 15.05%.Key Words: Leg Muscle Power, 100 Meter sprint